Trendline with Seasonal Adjustment Forecast for CF150 in Sport Mid Segment Product - Edison Lawby; Jani Rahardjo (Jurnal Titra, 2020)
PT XYZ is a motorcycle manufacturing company. PT XYZ distributes its products to 29 main dealers spread throughout Indonesia. main dealer X is the main dealer with the most inaccurate forecast accuracy with an accuracy forecast of 75,2%, because PT XYZ applies the forecast forecast accuracy of ±5%. main dealer x has a market share of 65% and when mapped to 9 segments there are 5 segments whose market share is below 65%. Of the five segments chosen the mid sport segment which has the most significant market share growth. the forecasting process is carried out in the mid sport segment and found that the CF150 product has a low stock. CF150 stock is below the KPI stock day monitoring implemented by PT XYZ so the product focused is CF150. After being implemented in the unit allocation process at PT XYZ, actual sales of CF150 were obtained in April of 31 units. With the actual sales, the forecast accuracy is 93.9% and it is still not said to be accurate for PT XYZ because it is still below its standard of 95%.